Contribution of the reservoir backflow to the eutrophication of its tributary: a case study of the Xiangxi River, China - Wenguang Luo; Xin Luo; Jing Lu; Ming Bo (Hydrology Research, 2022)
Based on the routine water quality monitoring data of the Xiangxi River and its main monitoring section from January 2014 to May 2016, the monthly dynamics of nutrient concentrations and fluxes were analyzed, and the relationship between the water exchange between the reservoir and the tributaries and the changes of nutrient fluxes in the river was established. The results showed that the nutrient flux in the Xiangxi bay estuary was negatively correlated with the reservoir reflux intensity, and the overall correlation coefficient was −0.52. Four nutrient indexes, total nitrogen, total phosphorus, ammonia nitrogen (), and soluble phosphorus, all showed the same regularity and characteristics, among which was particularly prominent. It can be concluded that the variation of nutrient salts in the water body of the tributary bay is mainly determined by the water exchange between the reservoir and the tributary. In addition, the change of chemical oxygen demand and chlorophyll a flux in the Xiangxi Bay and water exchange in the reservoir area were analyzed. We found that changes in the hydraulic conditions of the return flow in the reservoir area can destroy the suitable flow environment necessary for the survival of algae, thus preventing the proliferation of harmful algae. Therefore, by controlling the hydrodynamic conditions between the reservoir area and the tributaries and changing the degree of water exchange between them, the objective of improving the water environment in the Xiangxi Bay can be achieved to a large extent. HIGHLIGHTS The assessment method of water quality change in the reservoir bay was established.; The corresponding relationship between hydrodynamic conditions and water quality change in the reservoir area is discussed.; The water quality assessment method of Kuwan tributaries obtained in this study has broad application prospects.;